Spontaneous Perforation of Stomach in a Neonate - Sethi, Harish; Simalti, Ashish; Chauhan, SS; Chandra, Mukesh (Journal of Nepal Paediatric Society, 2016)
Spontaneous gastric perforation is not a very common entity. If not suspected and managed in time, this is uniformly fatal. Although documented as early as in1825 exact pathology remains unclear even to date. A case of spontaneous rupture in a term neonate is being presented as a case report. J Nepal Paediatr Soc 2015;35(3):301-303.